Inovasi Pembelajaran Literasi Untuk Siswa di SDN 1 Mancilan Mojoagung Jombang - Putra, Ino Angga; Airlangga, Primaadi; Iffah, Bidayatul Hubbil; Mustaghfirin, A’at; Ismah, Feniatul; Anwar, Putri Elsa Syintia; Rahmawati, Lusi (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2024)
Elementary school is the first level of formal education for students in pursuing education. Where education in elementary schools has a contribution in building students' knowledge base used at the next level of education, therefore the implementation of learning in elementary schools must run optimally so that the objectives of holding elementary school education can be achieved. Reading skills are a way to get information about something written. Reading and writing skills are skills that a person acquired after they enter school. Therefore, these two types of language skills are the main learning offerings for students in lower elementary schools. These two skills materials are presented in one initial reading and writing package. Reading and writing must be immediately mastered by students in elementary school because these skills are directly related to the entire student learning process at school. In relation to this, the community service team and SDN 1 Mancilan found 13 students from grades 3-6 who experienced difficulties in reading and writing. Based on this, the community service team carried out reading and writing guidance for the 13 students by applying learning media in the form of modules, learning media in the form of spelling circles and standing words using spelling, syllable, and word method approach. To increase students' interest in literacy, the community service team carried out socialization and training on making wall magazine for grade 5 and 6 students using the Learning by Doing or LBD method.